MEMBANGUN MOTIVASI KEWIRAUSAHAAN MASYARAKAT UNTUK MENINGKATKAN PEREKONOMIAN MELALUI PENDIDIKAN NONFORMAL - Jemsin Poyang; Ahmad Nizam; Chloe Rensana (Universitas Negeri Medan, 2025)
Entrepreneurship plays a strategic role in promoting sustainable local economic development, particularly in communities with limited access to formal employment. This study aims to analyze how nonformal education programs contribute to strengthening community entrepreneurial motivation and improving local economic resilience. The research employed a systematic literature review approach by analyzing peer-reviewed journal articles, policy documents, and scholarly books related to entrepreneurship education, motivation theory, and community empowerment. The findings indicate that entrepreneurial motivation is influenced by internal factors such as achievement orientation, self-efficacy, and autonomy, as well as external factors including training access, mentoring, family environment, and policy support. Nonformal education programs through entrepreneurship training, mentoring, and community based learning play a crucial role in enhancing entrepreneurial intention and business sustainability. The study concludes that strengthening entrepreneurial motivation through structured nonformal education interventions can significantly contribute to job creation, poverty reduction, and inclusive economic growth.